Design Experiment on Easy-to-Wear Warm Boots for Wheelchair Users (Journal of Fiber Bioengineering and Informatics, 2025)
To solve the problems of wheelchair users’ shoes and boots in the aspects of convenience, warmth, andcomfort in low-temperature environments and better meet their physiological and psychological needs,this paper proposes a structural design scheme of easy-to-wear and take-off warm boots based on a newtype of warm wadding. At the same time, the fuzzy mathematics comprehensive evaluation method wasused to select a new kind of flocculant with excellent thermal and wet comfort polyester fiber flocculantas the filling material for the follow-up warm boots. This paper has guiding significance and applicationvalue to the development and application of wheelchair users to put on and take off warm boots.